Fast and Slow Inhibition in the Visual Thalamus Is Influenced by Allocating GABAA Receptors with Different γ Subunits - Ye, Zhiwen; Yu, Xiao; Houston, Catriona M.; Aboukhalil, Zahra; Franks, Nicholas P.; Wisden, William; Brickley, Stephen G. (Frontiers in Cellular Neuroscience, 2017)
Cell-type specific differences in the kinetics of inhibitory postsynaptic conductance changes (IPSCs) are believed to impact upon network dynamics throughout the brain. Much attention has focused on how GABAA receptor (GABAAR) α and β subunit diversity will influence IPSC kinetics, but less is known about the influence of the γ subunit. We have examined whether GABAAR γ subunit heterogeneity influences IPSC properties in the thalamus. The γ2 subunit gene was deleted from GABAARs selectively in the dorsal lateral geniculate nucleus (dLGN). The removal of the γ2 subunit from the dLGN reduced the overall spontaneous IPSC (sIPSC) frequency across all relay cells and produced an absence of IPSCs in a subset of relay neurons. The remaining slower IPSCs were both insensitive to diazepam and zinc indicating the absence of the γ2 subunit. Because these slower IPSCs were potentiated by methyl-6,7-dimethoxy-4-ethyl-β-carboline-3-carboxylate (DMCM), we propose these IPSCs involve γ1 subunit-containing GABAAR activation. Therefore, γ subunit heterogeneity appears to influence the kinetics of GABAAR-mediated synaptic transmission in the visual thalamus in a cell-selective manner. We suggest that activation of γ1 subunit-containing GABAARs give rise to slower IPSCs in general, while faster IPSCs tend to be mediated by γ2 subunit-containing GABAARs.